Anticipating and Incorporating Stakeholder Feedback when Developing Value-Added Models - Balch, Ryan; Koedel, Cory (Education Policy Analysis Archives, 2014)
State and local education agencies across the United States are increasingly adopting rigorous teacher evaluation systems. Most systems formally incorporate teacher performance as measured by student test-score growth, sometimes by state mandate. An important consideration that will influence the long-term persistence and efficacy of these systems is stakeholder buy-in, including buy-in from teachers. In this study we document common questions from teachers about value-added measures and provide research-based responses to these questions. The questions come from teachers in Baltimore City Public Schools, who are evaluated using a combined measure of which value-added is one component. We focus on teacher questions about value-added because value-added generates the most concern from teachers. We also connect teacher concerns about value-added to other components of the evaluation system, such as classroom observations, although at present these other components have not garnered as much attention from teachers.